2021
DOI: 10.1101/2021.03.08.21253152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation hotspots, geographical and temporal distribution of SARS-CoV-2 lineages in Brazil, February 2020-2021: insights and limitations from uneven sequencing efforts

Abstract: The COVID-19 pandemic has already reached approximately 110 million people and it is associated with 2.5 million deaths worldwide. Brazil is the third worst-hit country, with approximately 10.2 million cases and 250 thousand deaths. Unprecedented international efforts have been established in order to share information about epidemiology, viral evolution and transmission dynamics. However, sequencing facilities and research investments are very heterogeneous across different regions and countries across the gl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…Of the five main circulating lineages, B.1.1.33 and B.1.1.28 were the most predominant, mainly in the initial period of the study. Our findings are supported by other Brazilian sequencing studies, which showed that B.1.1.33 and B.1.1.28 are the most prevalent lineages of the country, including South Brazil [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the five main circulating lineages, B.1.1.33 and B.1.1.28 were the most predominant, mainly in the initial period of the study. Our findings are supported by other Brazilian sequencing studies, which showed that B.1.1.33 and B.1.1.28 are the most prevalent lineages of the country, including South Brazil [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…The geographic distribution of lineages was evaluated in four RS-sampled regions since the first detection of VUI-NP13L in our sampling (Fig. 4 Southeast Brazil, on 9 March 2020 and then disseminated across the country 16,24,37,38 . This lineage was also associated with outbreaks in Argentina and Uruguay, countries bordering RS 38,39 .…”
Section: Temporal and Spatial Dynamics Of Sars-cov-2 Lineagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences evaluated in our study are restricted to 2020; therefore, we cannot rule out if the lineages are still active across southern Brazil. 16,18,20,23 . This lineage was also associated with secondary outbreaks in Argentina and Uruguay, countries bordering RS 18,24 .…”
Section: Discussionmentioning
confidence: 99%
“…According to an independent phylodynamic reconstruction, P.4.1 rapidly arrived in the southeastern and northeastern regions of Brazil and seems to have been exported to Japan, the Netherlands and England 23 . The success of the spread of P.4.1, beyond having important mutations in the spike protein (V1176F, D614G), also shared by P.2 and P.1 lineages, could be justified by the unique amino acid changes in ORF1a 16,26,27 . This gene is known to encode a polyprotein involved in the replication complex 28 .…”
Section: Discussionmentioning
confidence: 99%